Clinical outcomes of orthogonal plating to treat radial and ulnar fractures in toy‐breed dogs. (14th July 2021) - Higuchi, M.; Katayama, M.
Abstract : Objectives: To describe the results of orthogonal plating (OP) as a treatment for fractures of the radius and ulna in toy‐breed dogs. Materials and Methods: The medical records (June 2011 to April 2019) of toy‐breeds in which the OP technique using non‐locking cuttable plates was employed to treat radial and ulnar fractures were reviewed. The inclusion criteria included a bodyweight of 3.5 kg or less, fracture of the diaphysis of the radius and ulna of one or both forelimbs, and the availability of follow‐up radiographs. Revision surgeries were also included. Results: Fifteen limbs that underwent initial fracture repair and five that underwent revision surgery met the inclusion criteria. The radial and ulnar fractures healed in 19 limbs at the final follow‐up. Synostosis of the radius and ulna at the fracture sites was observed in one limb. Re ‐fracture after cranial plate removal was observed in one case. All dogs exhibited successful return of normal limb function at the final clinical and radiographic follow‐up (mean, 104.7 ± 67.1 days; median, 79.5 days; range: 35 to 248 days). Long‐term follow‐up data obtained via telephone interviews to owners or referring veterinarians were available for 15 cases and confirmed maintenance of normal limb function in all dogs (mean, 32.5 ± 17.6 months; median, 26 months; range: 11 to 69 months). Clinical Significance: OP allowed the successful open reduction of radial and ulnar fractures, facilitating bone union in both the radius and ulna and a return to normal limb function in a series of toy‐breed dogs.